2019
DOI: 10.1111/1365-2656.13139
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of species traits on predation risk in nature: A comparative study of butterfly wing damage

Abstract: Evading predators is a fundamental aspect of the ecology and evolution of all prey animals. In studying the influence of prey traits on predation risk, previous researchers have shown that crypsis reduces attack rates on resting prey, predation risk increases with increased prey activity, and rapid locomotion reduces attack rates and increases chances of surviving predator attacks. However, evidence for these conclusions is nearly always based on observations of selected species under artificial conditions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…B 288: 20202840 detrimental to survival (e.g. [38]); many species in the wild exhibit more hindwing damage [39]; and Pieris rapae and Morpho butterflies without hindwings remain able to evade predators (although at reduced height, speed and acceleration) [40,41]. Forewings, however, are critical for all stages of flight, from general flight to evasive manoeuvring [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…B 288: 20202840 detrimental to survival (e.g. [38]); many species in the wild exhibit more hindwing damage [39]; and Pieris rapae and Morpho butterflies without hindwings remain able to evade predators (although at reduced height, speed and acceleration) [40,41]. Forewings, however, are critical for all stages of flight, from general flight to evasive manoeuvring [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…We focused on three large‐bodied fruit‐feeding nymphalid butterfly species that are common in Kibale forest; Charaxes fulvescens (average female wing length 4.95 cm, male 4.50 cm), Euphaedra alacris (4.71, 3.81 cm) and E. medon (4.23, 3.37 cm; Valtonen et al, 2013; Molleman et al, 2020). Dietary restriction studies with wild‐caught individuals have shown that females of all three species can use amino acids from income for egg production (Molleman et al, 2008a; Molleman, Ding, Wang, & Carey, 2009), and that males (but not females) live longer when provided with amino acids in their diet (Molleman, Ding, Boggs, et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…While the fruit‐feeding butterfly community as a whole responds to rainfall (Valtonen et al, 2013), out of the three study species, a population response to rainfall was only detected in E. alacris and E. medon (Appendix S1). All three species are understory specialists (Molleman et al, 2006) that can fly rapidly (Molleman et al, 2020), have small spermatophores (Molleman, Grunsven, et al, 2005), are long‐lived (longevity records: C. fulvescens 230 days, E. alacris 253 days, E. medon 293 days; Molleman et al, 2007) and occur throughout the year with non‐seasonal abundance fluctuations (Valtonen et al, 2013; Appendix S1). They have been observed feeding on a variety of fruits, but may also feed on other substances such as sap oozing from trees (Molleman, van Alphen, et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The loss of wing margins and especially HW margins has a low impact on butterflies flying abilities [17] and may therefore have a limited impact on survival. Butterflies are indeed commonly observed flying in the wild with such wing damage [18]. The escape from predators after an attack might also be facilitated by enhanced fragility of the attacked parts of the wings.…”
Section: Introductionmentioning
confidence: 99%